Dynamics of Changes in Public Transportation Consumption Patterns Due to Fuel Price Increases - Dini Agustin; Eggy Alinugraha Hidayat; Gilang Sanjaya; Siti Alisa Putri Al-Zahra; Zahra Sabila Putri; Dadar Supriatna (Advances in Community Services Research, 2026)
Purpose: This study aims to analyze the potential impact of fuel price increases on economic conditions and public transportation consumption patterns in Bandung City, an urban area characterized by high mobility and transportation demand. Research Method: The study employed a descriptive qualitative approach using library research. Data were collected from peer-reviewed journal articles, policy documents, government reports, and statistical publications related to fuel pricing, inflation, transportation costs, mobility behavior, and public transportation. The literature was analyzed using content and comparative analysis techniques. Results and Discussion: The reviewed literature indicates that fuel price increases are associated with inflationary pressures, rising transportation costs, and changes in household expenditure allocation. In urban contexts, increasing fuel prices may encourage behavioral adaptation through more selective travel decisions, improved mobility efficiency, and greater consideration of public transportation alternatives. Bandung’s urban characteristics suggest that these impacts are particularly relevant due to its intensive transportation activities. Implications: The findings provide insights for policymakers in designing transportation and energy policies that support affordability, accessibility, and sustainable urban mobility. Future studies should use primary data to measure behavioral changes among Bandung residents directly. Originality: This study offers an integrated conceptual analysis of the relationship between fuel price increases, urban economic pressures, and public transportation consumption patterns within the specific context of Bandung City.